Health capital accumulation and effective utilisation: a theoretical framework based on an extended Cobb – Douglas production function - Mashevskaya, Oksana V.; Yuting, Zhang (Journal of the Belarusian State University. Economics, 2025)
Against the backdrop of the initiative «Healthy China» and the transformation of the demographic dividend, health capital has emerged as a critical determinant of national competitiveness and the long-term sustainability of economic development. Based on data from the China Statistical Yearbook, the National Health Commission of the People’s Republic of China, and United Nations World Population Prospects, this article analyses current trends in the formation of China’s health capital and the structural challenges associated with this process. Building on an extended Cobb – Douglas production function, we propose a theoretical framework that integrates health capital into macroeconomic output analysis and introduce a comprehensive multidimensional health human capital index (HHCI) encompassing four key dimensions. Furthermore, we present an integrated policy framework grounded in a life-course approach to health capital and multi-stakeholder engagement, offering practical strategies to promote its accumulation and improve its utilisation efficiency. The findings provide a solid theoretical and methodological basis for fostering high-quality, sustainable economic growth amid China’s ongoing demographic and institutional transformations.